Training and Trainer's challengers:The case of ABM Sarawak / Abdul Rahman Ahmad and Ikhwan Mohd Ibrahim - Ahmad, Abdul Rahman; Mohd Ibrahim, Ikhwan (2014)
The purpose of this study is to identify what challenges do the training and trainer' of ABM Wilayah Sarawak facing in construction industry training. The emergence of new technology together with new mind set of new generation of construction workers making their day to day working routine become challenging. The challenges becoming new bench mark to evaluate their effectiveness and their relevancies to their own world of work. Are they still relevance and how they want to maintained their relevancies in new environment? What do they need to do to maintain relevant and what are their needs? How ABM coping up with the changes needed by their employees? This study is mainly to extract or analyse this issues and to recommend necessary action for consideration in future.